2012
DOI: 10.1159/000334404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Dose Oxytocin and Dinoprostone for Labor Induction in Postterm Pregnancies: A Randomized Controlled Prospective Study

Abstract: Aims: The aim of this study was to compare the efficacy of oxytocin and dinoprostone in achieving successful labor induction and vaginal delivery in postterm women with an unfavorable cervix. Methods: Postterm women with an uncomplicated pregnancy and a Bishop score of ≤6 were randomized to receive either dinoprostone vaginal pessary (Propess®) or low-dose oxytocin. The primary outcomes were the length of the induction-to-delivery period and the incidence of vaginal delivery. Results: A total of 144 women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 12 publications
3
23
1
Order By: Relevance
“…Unfavorable cervix defined as a Bishop score ≤6. Cervical ripening was performed with intracervical prostaglandin E 2 gel or oxytocin [25]. Induction of labor with oxytocin infusion begun at 4 mU/min and increased by 4 mU/min every 20 min to a maximum of 40 mU/min.…”
Section: Methodsmentioning
confidence: 99%
“…Unfavorable cervix defined as a Bishop score ≤6. Cervical ripening was performed with intracervical prostaglandin E 2 gel or oxytocin [25]. Induction of labor with oxytocin infusion begun at 4 mU/min and increased by 4 mU/min every 20 min to a maximum of 40 mU/min.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial and venous umbilical cord gas parameters have been found to be unaffected by oxytocin augmentation or induction (11,13). Moreover Apgar scores, which indicate the well being of newborn infants, were shown to be statistically similar in women induced with dinoprostone and oxytocin (5,12). We found that all Apgar scores were ≥7, all umbilical artery pHs were above 7.10, and none of the newborns experienced fetal acidosis.…”
Section: Discussionmentioning
confidence: 97%
“…Uterine perfusion decreases during contractions, and increased uterine activity has negative effects on uteroplacental and fetoplacental circulation (11). Intravenous oxcytocin was shown to result in hyperstimulation in 8.3-11.1% of women and fetal distress in 15.9-18%, suggesting that oxytocin application during labor may trigger fetal oxidative stress (5,12). However, oxytocin did not have any negative effects on pH and did not increase perinatal risk (11,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations